Presentation: Social transformation through critical literacies: emerging priorities for contemporary Applied Linguistics - Tanzi Neto, Adolfo; Morgan, Brian; Nicolaides, Christine Siqueira (Calidoscópio, 2022)
Special Issue: Social transformation through critical literacies: emerging priorities for contemporary Applied Linguistics - celebrating three decades of the existence of the Brazilian Association of Applied Linguistics (ALAB).